IMPLEMENTING A GENRE-BASED APPROACH IN TEACHING SPOKEN EXPOSITION TEXTS TO EFL UNIVERSITY STUDENTS - Lukman Hakim; Iyen Nurlaelawati; Annisa Rahmadani (University of Kuningan, 2025)
The genre-based approach (GBA) has been utilized mainly in teaching writing, but its implementation in teaching speaking for an academic context has not been explored extensively. This research aims to examine how GBA was implemented in speaking the exposition text in the English as a foreign language (EFL) context and the outcomes of students’ spoken exposition performances. Using a case study design, this research involved 21 fifth-semester students from an English language education program in Indonesia who were enrolled in speaking for academic purposes. The data were collected from observations and the analysis of students’ speaking videos. The findings from observations show that the teaching and learning cycles have complied with the GBA cycle; however, the lecturer made modifications in the modelling stage, specifically using videos to exemplify speaking performance and deconstructing the video content. Then, the analysis of the students’ videos indicates that the students seemed to be able to present their exposition text in line with the generic structure and linguistic features. However, the data also revealed that some students struggled with pronunciation and grammar. Despite these challenges, this study has highlighted the importance of implementing GBA in helping students adhere to the exposition text’s generic structure and linguistic features. The findings of this research may suggest that GBA can be used not only to teach writing production but also to teach speaking skills in the EFL context.